Developmental cascades of social competence, achievement in school, and achievement on standardized assessments during the transition to adolescence and secondary school. (10th June 2019) - Okano, L.; Jeon, L.; Crandall, A.; Powell, T.; Riley, A.
ABSTRACT: Introduction: Social and academic functioning are cornerstones of positive youth development and important to later educational and health outcomes. Yet, little is known about how the timing and direction of relationships between social and academic functioning vary by the type of achievement assessed and how the transition to adolescence influences these relationships. Method: This study employs longitudinal structural equation modeling to examine the interrelationships of children's social competence, teacher ratings of school achievement, and standardized assessments of cognitive achievement in a cohort of 1048 children in the United States. Results: & Conclusions: Results identify 1) direct and indirect pathways from children's social competence in grades three and five to their school achievement in grades five and six; 2) significant pathways between school and cognitive achievement across all assessment points that decline in magnitude as students enter high school; 3) the magnitude of pathways between social competence and school achievement far exceed those between social competence and cognitive achievement; and 4) social and maturational factors account for variation in these functions but do not confound the timing and direction of the pathways from one to the other function. Given the importance of social competence and academic achievement to positive development, these findings demonstrate elementary school as an optimal and foundational period to implement universal interventions to optimize social functioning and prevent later academic difficulties in secondary school.